2014
DOI: 10.1089/acm.2013.0306
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Care Therapies and Pain in Hospitalized Children and Adolescents: A Retrospective Database Review

Abstract: Background: Complementary or integrative care therapies are promising adjunctive approaches to pain management for pediatric inpatients that are currently underused and understudied. The purpose of this study was to examine the potential benefits of integrative care therapies delivered to hospitalized children and adolescents at a large Midwestern academic pediatric medical center over a 1-year period. Methods: A retrospective chart review of an inpatient clinical database maintained by integrative care therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Our study addresses several gaps in the literature with regard to the provision of IM in US hospitals, as IM referral processes within an inpatient setting have not been studied previously. Although IM is increasingly being provided to US inpatients in areas such as oncology 14 15 and paediatrics, 16 17 hospitals with well-established IM offerings for inpatients are more prevalent internationally (eg, in Israel, 18 19 Germany 20 21 and China 22 ). However, operational processes and cultural contexts surrounding acceptance of IM are substantially different internationally in comparison with the USA, where IM offerings are less widespread and assimilated.…”
Section: Discussionmentioning
confidence: 99%
“…Our study addresses several gaps in the literature with regard to the provision of IM in US hospitals, as IM referral processes within an inpatient setting have not been studied previously. Although IM is increasingly being provided to US inpatients in areas such as oncology 14 15 and paediatrics, 16 17 hospitals with well-established IM offerings for inpatients are more prevalent internationally (eg, in Israel, 18 19 Germany 20 21 and China 22 ). However, operational processes and cultural contexts surrounding acceptance of IM are substantially different internationally in comparison with the USA, where IM offerings are less widespread and assimilated.…”
Section: Discussionmentioning
confidence: 99%
“…Another primary reason that complementary methods have turned out highly beneficial in inpatient paediatric settings can be seen from the infants’ relaxation, especially in agitated babies with NAS [ 40 ]. It has also been shown that the combination of ear and body acupuncture is very successful [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, the data collected were entered into a network-secured clinical database, along with standard demographic patient information, reason for integrative care referral, the type of integrative care therapy received, and the duration of the intervention. 36 Approval for this retrospective chart review was obtained from the hospital's institutional review board, and ethical standards were maintained throughout the research process.…”
Section: Methodsmentioning
confidence: 99%
“…Initial data cleaning was conducted on the full clinical database as described in our previous paper 36 ; the full database also contained child and adolescent data, while this investigation included only those assessed using the Neonatal Infant Pain Scale to create a previously unreported and distinct sample of 213 patients seen in the NICU. While the full clinical database included multiple interventions and even multiple hospitalizations for some patients, only the first intervention during the first hospitalization in the study period was included in analysis to limit potential effects from patients acclimating to therapies over time.…”
Section: Methodsmentioning
confidence: 99%